The phenomenon of word-formation hybrids in the language of fashion - Choromański, Maciej (Papers in Linguistics, 2020)
The aim of this article is to present the phenomenon of word-formation hybrids characteristic of the contemporary German language as visible in the language of fashion. From the linguistic perspective, the phenomenon of combining native and non-native language elements is interesting, as nowadays many language users tend to employ such combinations more and more often. Firstly, the concepts of borrowing and integrated and non-integrated foreign words were clarified. Further on, the focus was placed on the term word-formation hybrid, as well as the issue of the language of fashion. Based on the theoretical foundations, the corpus study was conducted in accordance with three criteria: morphological, foreignlingual and semantic. Moreover, the spelling aspects of word forming hybrids and the number of components comprising them were analysed.